Self and viral peptides can initiate lysis by autologous natural killer cells - Mandelboim, Ofer (The National Academy of Sciences of the USA, 1997)
Natural killer (NK) cells are inhibited by specific allotypes of class I major histocompatibility complex ligands recognized by polymorphic inhibitory receptors (e.g., NKIR1 and NKIR2). NK1- and NK2-specific clones recognize two groups of HLA-C allotypes that are distinguished by a dimorphism at residue 80 in the α1 helix (αLys-80 and αAsn-80, respectively). “Empty” HLA-Cw7 expressed in peptide transporter-deficient cells and HLA-Cw7 loaded with several peptides each functioned as inhibitory ligands for NK2 lines and clones. However, loading of HLA-Cw7 with two other peptides derived from glutamic acid decarboxylase or coxsackie virus (each of which has been associated with autoimmune diabetes mellitus) abrogated this inhibitory recognition. Both peptides contained Lys at P8 of the epitope. Substitution of P8 with Ala or two other basic amino acids, His and Arg, resulted in peptides that were inhibitory, as were peptides with P8 Val, Glu, or Asn. The manner in which a Lys at P8 might affect recognition is discussed, together with a hypothesis for a novel mechanism by which an autoimmune disease might be initiated.